PERSONALITY INFORMATION CULTURE CONDITIONS OF INFORMATIZATION OF SOCIETY - Volkova, N.V. (Pedagogy of Higher and Secondary Education, 2022)
The article deals with the question offorming of information culture of a personality in the condition of swift informatization of society.